Actual problems of legal regulation of the integration of compatriot (Journal of actual problems of jurisprudence, 2018)
In a scientific article, the author examines in detail the problems of legal regulation of the integration ofcompatriots on the basis of analysis of the experience of legal systems of Germany, Poland and Kazakhstan.This paper makes recommendations for improving the legislation and its implementation. Using comparativelegal analysis to identify common and specific features, advantages and disadvantages of integration issuescompatriots in those countries.Keywords: compatriot, integration, legal regulation, repatriation, immigrant, foreign experience.